“The Singularity is near!” Visions of Artificial Intelligence in Posthumanism and Transhumanism. - Krüger, Oliver (International Journal of Interactive Multimedia and Artificial Intelligence, 2021)
Over the past 20 years, the idea of singularity has become increasingly important to the technological visions of posthumanism and transhumanism. The article first introduces key posthumanist authors such as Marvin Minsky, Ray Kurzweil, Hans Moravec, and Frank Tipler. In the following, the concept of singularity is reviewed from a cultural studies perspective, first with regard to the cosmological singularity and then to the technological singularity. According to posthumanist thinkers the singularity is marked by the emergence of a superhuman computer intelligence that will solve all of humanity’s problems. At the same time, it heralds the end of the human era. Most authors refer to the British mathematician Irving John Good’s 1965 essay Speculations Concerning the First Ultraintelligent Machine as the originator of the idea of superintelligence. Individual elements of the singularity idea such as the impenetrable event horizon, the frontier and the ongoing acceleration of progress are contextualized historically and culturally.